The subject in question : Sartre's critique of Husserl in The transcendence of the ego - Priest, Stephen (Routledge studies in twentieth century philosophy., 2000)
The Subject in Question provides a fascinating insight into a debate between two of the twentieth century's most famous philosophers - Jean-Paul Sartre and Edmund Husserl - over the key notions of conscious experience and the self. Sartre's The Transcendence of the Ego, published in 1937, is a major text in the phenomenological tradition and sets the course for much of his later work. The Subject in Question is the first full-length study of this famous work and its influence on twentieth-century philosophy. It also investigates the relationship between Sartre's idea.